Prediction of Online Purchase Decisions: A Case of Nongshim Instant Noodles Consumers - Ellena Nurfazria Handayani; Melani Quintania; Firsan Nova; Siti Khoiru Risma (Universitas Warmadewa, 2022)
This study is specifically aimed at predicting online purchasing decisions on the influence of the halal label and the lifestyle of instant noodle consumers of Nongshim products, either simultaneously or partially. This type of study is an explanation based on causal-and-effect with quantitative analysis. The source data consist of primary data enhanced. The sampling technique utilized was purposive sampling with a Rao calculation with a precision level is 0.05. The final sample was obtained from 97 respondents. Analysis method used the utilize of the multiple regression linear. The results inferred that only lifestyle is able to prediction towards online purchase decisions while the halal label is not able to predict. Furthermore, halal label and lifestyle are able prediction towards online purchase decisions simultaneously.